Physical activity and biological risk factors clustering in pediatric population - J. C. Ribeiro (2004)
Background. From a preventive point of view, it is especially important to investigate the life style risk factors connected to cardiovascular disease (CVD) biological risk factors clustering. The purposes of this study were (1) to determine in pediatric population the coexistence of biological cardiovascular disease risk factors (high blood pressure (HBP), percentage of high fat mass (%HFM), and high total cholesterol (HTC)) and (11) to study the relationship between low physical activity, a lifestyle risk factor, with those biological risk factors. Methods. This study comprised 1461 children (699 males and 762 females) aged between 8 and 15 years old. The following measurements were carried out: blood pressure, percentage of fat mass, total cholesterol (TC), and physical activity. The quartiles, adjusted for age and gender, were the criterion used to classify the subjects at risk. Odds ratios and confidence intervals at 95% were used to study HBP, HTC, and %HFM clustering in both genders. Multinomial logistic regression was used to investigate the relationship between clustering and physical activity index (PAI). Results. The findings of this study indicated that there is clustering for the biological risk factors, specially between HBP and %HFM for females. It can be observed that about half of the subjects had at least one biological risk factor. Conclusions. The results of the present study suggest that children and adolescents with higher PAI have a lower number of biological risk factors for CVD.